CFD modeling of reactive absorption of CO2 in aqueous NaOH in a rectangular bubble column: Comparison of mass transfer and enhancement factor model. (2nd February 2021) - Liu, Junda; Zhou, Ping; Liu, Liu; Chen, Si; Song, Yanpo; Yan, Hongjie
Highlights: The Henket1 model was found to be the most accurate among the assessed four mass transfer models. The enhancement factor model of Hlawitaschka performs better than that with a constant of 1. The mass transfer model has very little effect on pH variation at the end of the reaction. Abstract: Presently various mass transfer rate models have been developed to predict the mass transfer rate in the column. Also, different enhancement factor models were proposed to include the influence of chemical reaction on mass transfer process. However, a comprehensive assessment of these models has rarely been performed, leaving the model accuracy arguable. In this study, four typical mass transfer rate models and two enhancement factor models were employed to simulate the gas-fluid mass transfer behaviors of a bubble plume rising in a rectangular bubble column, and their accuracies were evaluated by comparing the simulation results with the published experimental data. The results show that the Henket1 model is the most accurate among the assessed four mass transfer models. The model of Hlawitschka performs better than that with a constant enhancement factor. The mass transfer model has very little effect on pH variation at the end of the reaction.